Storybook ending : a novel - Alexander, Poppy (Avon, An Imprint of HarperCollinsPublishers, 2024)
"For children’s book author Imogen, an idyllic life in the English countryside seems like the perfect fit for her and her husband. But when tragedy strikes, Imogen is left widowed, and finds herself moving into Storybook Cottage alone with only her monstrously narcissistic cat for company. After discovering she is pregnant, Imogen grows determined to embrace a new start in Middlemass, with its duckpond, cricket matches and village fêtes. The only thing Imogen can’t seem to shake is her neighbor - a brooding, artisan blacksmith named Zach - who she can’t quite decide is friend or foe. That is until she realizes, thanks to an arcane clause in her deeds, that Zach is not just an artist, but lord of the local manor house. He has the power to take her home and leave her completely broke. Devastatingly - he seems keen to do exactly that. Yet, Imogen finds herself drawn to him nonetheless. And in her darkest hour, Zach may just be the bright spot to save Imogen in more ways than one." -- Back cover